Extending the Applicability of In Ovo and Ex Ovo Chicken Chorioallantoic Membrane Assays to Study Cytostatic Activity in Neuroblastoma Cells - Merlos Rodrigo, Miguel Angel; Casar, Berta; Michalkova, Hana; Jimenez Jimenez, Ana Maria; Heger, Zbynek; Adam, Vojtech (Frontiers in Oncology, 2021)
Purpose The chick chorioallantoic membrane (CAM) assay can provide an alternative versatile, cost-effective, and ethically less controversial in vivo model for reliable screening of drugs. In the presented work, we demonstrate that CAM assay (in ovo and ex ovo) can be simply employed to delineate the effects of cisplatin (CDDP) and ellipticine (Elli) on neuroblastoma (Nbl) cells in terms of their growth and metastatic potential. Methods The Nbl UKF-NB-4 cell line was established from recurrent bone marrow metastases of high-risk Nbl (stage IV, MYCN amplification, 7q21 gain). Ex ovo and in ovo CAM assays were optimized to evaluate the antimetastatic activity of CDDP and Elli. Immunohistochemistry, qRT-PCR, and DNA isolation were performed. Results Ex ovo CAM assay was employed to study whether CDDP and Elli exhibit any inhibitory effects on growth of Nbl xenograft in ex ovo CAM assay. Under the optimal conditions, Elli and CDDP exhibited significant inhibition of the size of the primary tumor. To study the efficiency of CDDP and Elli to inhibit primary Nbl tumor growth, intravasation, and extravasation in the organs, we adapted the in ovo CAM assay protocol. In in ovo CAM assay, both studied compounds (CDDP and Elli) exhibited significant (p < 0.001) inhibitory activity against extravasation to all investigated organs including distal CAM. Conclusions Taken together, CAM assay could be a helpful and highly efficient in vivo approach for high-throughput screening of libraries of compounds with expected anticancer activities.